Polyvinyl alcohol plant - Reyes, Gloria Z.; Nacpil, Arturo N.; Capuras, Jose Y. (Diliman, Quezon City College of Engineering, 1971)
This plant is designed to produce 2000 metric tons of a 99 percent (mole basis) hydrolyzed Polyvinyl Alcohol Resin, using the base-catalyzed process of hydrolysis in the replacement reaction between the acetate in the polyvinyl acetate and the hydroxyl group in the methanol to form the resin which by an enhanced syneresis effect due to the mixed methanol-methyl acetate solvent mixture, separates as a solid from the liquid reacting mixture. In the hydrolysis of polyvinyl acetate, a backmix reactor is used. A high RPM agitator is needed so as to mix readily the dissolved polyvinyl acetate beads in the mixed methanol-methyl acetate solvent with the dissolved sodium hydroxide catalyst. The base-catalyzed hydrolysis is chosen because of the high conversion it is capable of and since it is readily available from the literature. Acid-catalysis is slower. With this output of 2000 MT annually, an investment of around 1.3 million dollars is needed and around 2.9 million dollars is needed for the operating cost yearly. A gross income of 3.2 million dollars is realized from the products. It would appear, as the break even chart shows it, that although it is quite feasible to operate the plant, the shutdown point is quite near the break-even point, making the operation risky. The rate of return on investment and the payout time before taxes are 21.1 percent and 2.45 years respectively, and after taxes are 15.8 percent and 4.2 years, respectively.
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design
Keywords: Factories--Design and construction; Chemical plants; Polyvinyl alcohol